PENGARUH INVESTMENT OPPORTUNITY SET TERHADAP NILAI PERUSAHAAN DENGAN MEDIASI KEBIJAKAN DEVIDEN [Studi Empiris pada Emiten yang Tergabung dalam Index LQ45] - Billy Dharmawan; Fahrul Riza (Business Management Journal, 2019)
This study l examine whether IOS and dividend policy have a positive direct effect on firm value, and whether dividend policy mediates the indirect influence of IOS on firm value on companies incorporated in LQ45. Pooled Least Squares analysis method was used. IOS was  proxied with MVBVE, and dividend policy as a mediating variable was proxied with DPR. Firm value was  proxied with  Price Earning Ratio (PER). The samples taken were 27 companies from the population, namely companies incorporated in the LQ 45 index. The samples were chosen purposely, namely companies that were consistently in the LQ 45 index group for three consecutive years (2015-2017). Investment Opportunity Set has a significant positive effect on Company Value. Dividend policy has a significant positive effect on Corporate Value and dividend policy mediates partially the effect of no IOS on firm valueKeywords:  Investment Opportunity Set, Devidend Payout Ratio, Firm Value